128 Pregnancy and calving rates of beef cows comparing the sex-selected semen to conventional semen using timed artificial insemination. (28th November 2020) - McMurray, Jennifer; DeCarlo, Andrea N; Long, Nathan; Pratt, Scott
Abstract: A study was conducted over three years to determine if differences in pregnancy rates existed between the use of commercially available sex-selected (SEXED) or conventional semen (STD) coupled to fixed-time artificial insemination (TAI). A total of 240 (2016: n = 80; 2017: n = 95; 2018: n = 65) primi- or multiparous Angus or Angus-cross cows being at 45 days post-partum or greater were blocked by weight and BCS and assigned to be inseminated using SEXED semen or STD semen. Artificial insemination was performed by the same AI technicians (n = 3) across all years. All cows were subjected to estrous synchronization and insemination using the SEXED semen or STD semen with TAI between 63 and 66 h post-CIDR removal. Fourteen days post-TAI all cows were exposed to bulls for natural service. Cows were subjected to transrectal ultrasonography at day 30 and day 45 post-TAI to determine pregnancy rates and calving dates in the subsequent calving seasons were recorded to determine calving rates to TAI. Pregnancy rates were compared using a Chi-square test of two proportions. All statistical calculations were performed using JMP software and statistical significance was based on p-values less than 0.05. Pregnancy rates at day 30 and day 45 were 39.67% and 48.76% for SEXED and 47.90% and 54.62% for STD, respectively (P > 0.05). The percentage of calves born to TAI pregnancies for sex-selected semen and conventional semen were 22.31% and 40.34%, respectively (P < 0.05). These data indicate that the use of sex-selected semen can give similar pregnancy results to conventional semen in beef cow operations using TAI at day 30 of gestation; however, there was a reduction in the number of offspring to TAI comparing calving dates to animals pregnant at day 30.